Is There Any Role for D3 Lymphadenectomy in Gastric Cancer? - Douridas, Gerassimos N.; Pierrakakis, Stefanos K. (Frontiers in Surgery, 2018)
Although D2 constitutes the level of lymph node dissection which most surgical associations endorse in their treatment guidelines for gastric cancer more extended D3 dissection has also been attempted to improve oncologic outcomes. Existing literature pertinent with the provisional therapeutic impact of D3 lymphadenectomy in advanced gastric cancer is studied in this mini review. Seven non-randomized comparisons, three randomized trials and five meta-analyses, almost exclusively of Asian origin, were identified and examined. D3 compared to D2 lymphadenectomy consistently and significantly proved to be associated with a “heavier” iatrogenic surgical trauma translated to more blood loss, prolonged operative time, higher relaparotomy rates and post-procedural surgical and non-surgical morbidity. Oddly mortality in most of these series did not reach statistical significance a fact probably attributed to Asian surgical expertise and/or methodologic drawbacks. All existing evidence and their meta-analyses, including a well-designed RCT from Japan (JCOG), failed to support a clear overall survival benefit linked to D3 dissection thus excluding the procedure from current treatment algorithms. The Italian GC research group, analyzing their database, proposed tumor histology, macroscopic type, size and location as selection criteria for D3 dissection provided surgical expertise is available. Recently, a phase II clinical trial from Japan reported a3 -year survival rate of 59% in patients with clinically involved para-aortic nodes treated with neoadjuvant chemotherapy followed by D3 lymphadenectomy, rekindled the issue. Future multicenter randomized trials should test the extend and after effect of lymphadenectomy in gastric cancer combined with modern chemotherapeutic agents in multimodal treatments.